Creating reports with SQL server 2012 reporting services - Snider, Dallas H.; Safari eBooks ([Birmingham, U.K.] : Packt Pub., 2013)
"Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. The content is delivered in a concise, conversational style that emphasizes efficiency in development while empowering you to maximize the functionality and impact of your reports created with SQL Server Reporting Services. Creating Reports with SQL Server 2012 Reporting Services is designed for those who have a working knowledge of SQL and who need to deliver business intelligence via impressive, interactive reports. You will need a version of SQL Server 2012 that includes the SQL Server Data Tools. This thorough course requires basic experience with SQL Server and reporting."--Resource description page.
Title from title screen.
At head of title: 7180EN.
Date of publication from resource description page (Safari, viewed Jan. 27, 2014).
Presenter, Dallas H. Snider.
Keywords: SQL server; Client/server computing; Business intelligence -- Computer programs; Database management; Electronic books